Keterampilan Komunikasi Lisan Mahasiswa Pada Perkuliahan Sosiologi Antropologi Pendidikan - Saroinsong, Djony Max (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
Communication skills are important to convey ideas well, help in the process of preparing a frame of mind, and are the basis for being able to solve problems. This study aims to describe the level of oral communication skills of university students in educational anthropology sociology lectures. This research is a descriptive quantitative research and was conducted in two academic years (2022/2023 and 2023/2024) at the Nonformal Education Study Program, Universitas Negeri Manado. The research subjects consisted of 15 students who contracted sociology and anthropology of education courses in the two academic years. The data collection technique used was observation. In making observations, researchers used observation sheets as research instruments. The data analysis technique used descriptive statistics. The results showed that: oral communication skills on indicator 1 'expressing opinions and listening to other people's opinions' showed 84% including in the competent category; indicator 2 'mastering presentation material' showed 69% including in the less competent category; indicator 3 'delivering discussion results systematically and clearly' showed 76% including in the competent category; indicator 4 'asking questions to lecturers or other students' showed 81% including in the competent category; and indicator 5 'being able to answer questions from lecturers or other students' showed 68% so that it was included in the less competent category. Based on the research that has been conducted, it is found that the level of oral communication skills of students in sociology anthropology education lectures is 76%, which is included in the competent category.